Ecological Aspects of the Formation of Regraded Solonchak in the Terek-Kuma Lowland of the Caspian - G. N. Gasanov; Z. M. Asadulaev; T. A. Asvarova; Z. U. Gasanova; K. M. Gadzhiev; R. R. Bashirov; A. S. Abdulaeva; Z. N. Akhmedova; M. R. Musaev; N. R. Magomedov; A. А. Aytemirov; S. L. Desinov (Юг России: экология, развитие, 2020)
Aim. To reveal the basic patterns and principles of formation on the surface of crusty solonchak of an aeolian-accumulative horizon and its positive transformation at the taxonomic level.Material and Methods. On the surface of crusty solonchak there is formed a layer of silt-sand fractions with seeds of wild phytocenoses which move/перемещаюихся over the surface of the soil under the influence of atmospheric processes with the utilization of woody material protruding above the soil surface to 0.2 m. Analyses, surveys and observations were carried out of the key parts (for investigation - under the aeolian layer) of the crusty solonchak transformed through the dynamics of humidity, lowering of soil moisture (SC), granulometric composition, chemistry and level of soil salinity, as well as determination of the species composition of the phytocenoses and the accumulation of phytomass by plants.Results. The possibility was revealed of a positive transformation within eight years of a layer of silt-sand fractions with seeds of wild phytocenoses in the Wael humus horizon with a capacity of 5 cm ± 0.8 cm and containing 1.26% of humus. The type of salinization remains sulphate-chloride but the level of salinization decreases from very strong in the 0-5 layer to weak one in the 6-15 cm layer - on average. The profile of the crusty solonchak Скк [AJk - AJ,s - BCA,s - Cca,s] is changed to that of regraded solonchak Ckw [Wael - AJ,s - BCA,s - Cca,s]. The granulometric composition of the soil is improved and a productive phytocenosis is formed.Conclusion. The positive transformation of crusty solonchak to regraded contributes to the reduction of soil deflation and of aerial contamination by dust particle fractions, the lowering of carbon emissions from the soil and of the natural greenhouse effect, the increase of the utilization coefficient of photosynthetically active radiation (PAR) and the prevention of excessive overheating of the soil and atmosphere.